If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 27 = 3x + 9 Reorder the terms: 27 + x = 3x + 9 Reorder the terms: 27 + x = 9 + 3x Solving 27 + x = 9 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 27 + x + -3x = 9 + 3x + -3x Combine like terms: x + -3x = -2x 27 + -2x = 9 + 3x + -3x Combine like terms: 3x + -3x = 0 27 + -2x = 9 + 0 27 + -2x = 9 Add '-27' to each side of the equation. 27 + -27 + -2x = 9 + -27 Combine like terms: 27 + -27 = 0 0 + -2x = 9 + -27 -2x = 9 + -27 Combine like terms: 9 + -27 = -18 -2x = -18 Divide each side by '-2'. x = 9 Simplifying x = 9
| -x+29=2x+8 | | 5x-9=x+23 | | x-6=4x+21 | | -x-6=x+8 | | -x+20=x+6 | | -2x-25=x+2 | | ln^2(x)+9=0 | | 4x+25=x+7 | | (5x-4)*(12x+6)=0 | | -2x-15=x+6 | | 6x+32=2x+4 | | x-17=5x+15 | | 5x-5=x+23 | | 12x^2-145x+12=0 | | 60-8x=-4 | | x+(0.09*x)+12=300 | | X^3-2x=1.5 | | 13.78+x=15.07 | | X^2+10x=52 | | 42x=41x+9 | | (X+5)+(x+5)+x+x=62 | | 6x+11=-29-2 | | 6x+11=-26-2x | | 100/9.1 | | 3x*x-17x-6=0 | | 3x*2-17x-6=0 | | 100=40/12 | | x+27=(x+6)*5 | | 1+2/12=2x/12 | | z^2-(4-2i)z+11-4i=0 | | 1+1/12=1x/12 | | 1/a=3 |